LINGUACULTURAL PROBLEMS IN TRANSLATING EUPHEMISMS IN UZBEK AND ENGLISH MEDIA DISCOURSE (Journal of Multidisciplinary Sciences and Innovations, 2025)
This study examines the linguacultural challenges encountered in translating euphemisms between Uzbek and English media discourse. Through a comparative analysis of 120 euphemistic expressions collected from various media sources, this research identifies key translation problems including cultural specificity, semantic gaps, and pragmatic equivalence issues. The study reveals that euphemisms often carry culture-specific connotations that cannot be directly transferred between languages, requiring translators to employ various strategies such as functional equivalence, descriptive translation, and cultural adaptation. The findings demonstrate that successful euphemism translation requires not only linguistic competence but also deep cultural understanding and sensitivity to social taboos in both source and target cultures. This research contributes to translation studies by providing insights into the complex relationship between language, culture, and social attitudes in media communication.